PENDIDIKAN KARAKTER DALAM NOVEL RELIGIUS - Indrawati Indrawati (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2014)
Character Building is a conscious effort to cultivate a personality as the distinguishing feature between one individual to individual. Personality that includes how to behave and how to think in terms of personal and social activities. Character building works on various aspects of moral education, civic education, and character development. Each component provides a pressure difference on what is important and what should be taught. It must be multilevel and multichannel as unlikely to be implemented by one party alone. Formation needs exemplary character, the real behavior in the setting of an authentic life and not bias built instantly. Therefore, character education must be a moral movement that is holistic, involving various stakeholders and paths, and takes place in the setting of alamiah.Novel life is a form of modern literature. As a form of literature, he presents something expressive. The story is in the literature are usually sourced from the fictitious but does not rule out also sourced from the real thing. Literature for some people keep a mistery. Eventhough, Thus, literature, especially the novel contains certain values such as kindness that can affect the life and virtues of some one lifes. Virtues that are offered in the novel and capable captured by the public usually is a novel written by emphasizing the moral goodness packed in implicit mandate. Novelist sometimes not explicitly stated mandate contained in the novel. Everything is left to the reader to find his own mandate that novel. In this case the novel that made the object of study is a novel titled